Positive Politeness Strategies in Switched Movie by John K.D. Graham - Cici Yoseka; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of this research was to find out the positive politeness strategies in Switched movie. Switched movie was released in 2020. This movie was about the exchange of soul between two girls who have many differences in their life. The utterances of the characters in the movie were used as the data. The qualitative research method was used in this research. Observational method and non-participatory technique were used in the process of collecting the data. Then, the pragmatic equalizing method by Sudaryanto (2015) used in analyzing the data based on theory by (Brown & Levinson, 1987). The researchers found 15 utterances spoken by the characters in the movie. Use in-group identity markers and avoid disagreement were the two dominant strategies used by the characters throughout the movie. Another strategies found were exaggerate (interest, approval, sympathy with the hearer), the presuppose/rise/assert common ground, assert or presuppose speaker's knowledge and concern for the hearer's wants, includes both the speaker and the hearer in the activity, and assume or assert reciprocity. However, in the end there were some strategies not found in the selected data source.Keywords: politeness, positive politeness strategies, pragmatics